Asset Level Heterogeneity, Competition and Export Incentives: The Role of Credit Rationing - Sugata Marjit; Moushakhi Ray (Center for Economic Studies and ifo Institute (CESifo), 2020)
Firm heterogeneity is mostly discussed in the literature from the viewpoint of productivity differential. In contrast this paper recognizes wealth heterogeneity as an important factor that results in firm heterogeneity. The issue of wealth heterogeneity and export incentive through credit market imperfection over the life cycle of a firm remains largely unaddressed in the literature. This paper studies the dynamics of wealth heterogeneity and export incentive of credit rationed firms through asset building. The theoretical and empirical results indicate that an increase in the initial level of competition implies greater export incentive. However, over the life cycle of a firm, the role of competition is impacted by the intensity of capital accumulation and the initial level of wealth. Greater local competition before the entry of firms in the export market hurts export incentive by limiting cash flows and asset build up. Thus low profits due to competition allows firms to look for export opportunities but lower cash flows hurt such incentives.
Keywords: F10; F14; G10; G20; 330; export incentive; credit market imperfections; technology; competition; asset level heterogeneity